Study on the impact of hometown resource endowment on farmers’ rural-urban migration decisions against the background of “dual carbon” - Gao, Ping; Shen, Suyan; Yang, Zhenyu; Ji, Zheyan (Frontiers in Environmental Science, 2024)
In the context of "carbon peaking" and "carbon neutrality", this article explores the logic of farmers' migration decision-making under the land use behavior of urban and rural land occupation. This article also examines the role of hometown resource endowments led by homesteads, in farmers' land use and migration decisions. Using the China Migrants Dynamic Survey (CMDS) data, this study details the impact of hometown resource endowmentmainly residential landon farmers' migration decisions. The results show that: (1) owning homesteads and contracted land had a significant impact on farmers' settlement in cities, while the dividend effect from village collectives is not significant. In addition, using the administrative level of the hometown to measure whether there is a particular convenience in terms of location, this special "resource endowment" also has a significant positive role in family migration decision-making. (2) As the main hometown resource endowment for farmers, owning homestead and contracted land has a significant negative impact on both household and individual migration farmers. Moreover, owning homesteads has a greater impact on the decision of whole family migration farmers to settle in cities, and the lock-in effect of homesteads will reduce the probability of whole family migration to settle in cities by 21.1%.(3) Results of regional comparative analysis also show that owning homesteads and contracted land in the eastern region has a significant positive effect on the settlement of household migration farmers in cities, while it has a negative inhibitory effect in the central and western regions.